Elucidating Flood Disaster Problems in the World Capital Cities: Analyzing the Role of Humantrain Supply Chain - Muzani Muzani (International Journal of Supply Chain Management, 2020)
Jakarta is one of the cities that is often hit by floods. The problem of flooding in Jakarta is actually not a new thing. Many factors make Jakarta city vulnerable to flooding. These factors are natural and anthropogenic factors. These natural factors are: (1) Jakarta is located in the lowlands near the coast, (2) there are 13 rivers flowing through Jakarta, and (3) the high annual rainfall in the Ciliwung watershed ( 3000 mm). While anthropogenic factors are: (1) landscape changes due to high competition in land-based economic activities, (2) poor urban and rural spatial planning, and (3) lack of integrated institutional capacity and arrangements, especially in cross-border administration (especially Jakarta and West Java provinces). Lastly, our study has highlighted the need and significance of humantrain supply chain during the flood and similar other disasters. It is believed that humantrain supply chain is entirely different from commerical supply chain and may play a big role while addressing the issue of flood risk as faced by the community members.